Pengaruh Keamanan, Fitur Promosi dan Manfaat Uang Elektronik (Electronic Money) Terhadap Perilaku Konsumtif - Cindi Aulia Fatika Sari; Isyfa Fuhrotun Nadhifah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Technological developments in the financial world have encouraged more students to use and take advantage of electronic money, which ultimately changes their consumption behavior. The purpose of this study is to reveal how security factors, promotional features, and the benefits of electronic money affect student consumption levels. This study involved students from the Faculty of Economics and Business, Nahdlatul Ulama Islamic University, Jepara, who are accustomed to using electronic money for daily transactions. The sampling method used was purposive sampling, with 96 respondents calculated based on the Slovin formula. Data were obtained through a Likert scale questionnaire, then analyzed using the Partial Least Square (PLS) approach through the SmartPLS application. This analysis process included an evaluation of the measurement model (outer model) to assess validity and reliability, as well as a structural model (inner model) to test the impact between the research variables. The findings indicate that the security aspect has a positive and significant influence on student consumption behavior. Similarly, the promotional feature also shows a positive and significant influence on their consumption. On the other hand, the benefits of Electronic Money actually have a negative and significant effect on students' consumptive behavior.